Body image law : revolutionising images of thin-ideal women - Bromberg, Marilyn (Routledge research in fashion law., 2026)
"This book examines the effectiveness and limitations of existing body image law, and proposes evidence-based regulatory alternatives informed by public health and psychology research. Poor body image affects millions of people worldwide, and, despite the body positivity movement, the pressure on women in Western countries to have smaller bodies continues to cause significant harm to many. This book contributes to improving this, through drawing on evidence from research which outlines the harm excessive social media use and exposure to models with smaller bodies can cause to an individual's body image. It explores the regulatory efforts of governments in Israel, France and Norway which passed Body Image Laws, and failed attempts to pass bills in this area in Canada, the United Kingdom, Brazil and the United States. This book analyses the outcome of BMI requirements for catwalk fashion models, warning messages on digitally altered images and prosecuting pro-anorexia content creators. It asks why the current forms of body image law do not align with significant findings from public health and psychology. This book offers a compelling, evidence-based overview of body image as it intersects with law. It argues that body image law in its current form is unlikely to be effective, and makes suggestions for evidence-based approaches instead. This book will be of interest to researchers concerned with body image and the law as it relates to public health law, social media law and advertising law and anyone who has poor body image, an eating disorder or knows someone who has"-- Provided by publisher.